2016
DOI: 10.3233/rnn-150605
|View full text |Cite
|
Sign up to set email alerts
|

Steroid/Antiviral for the treatment of Bell’s palsy: Double blind randomized clinical trial

Abstract: The combination of steroid and antiviral treatment increases the possibility of recovery in moderately severe to complete acute Bell's palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Of these, 3,228 were excluded and 190 records passed for full‐text screening, of which 167 lacked the eligibility criteria. Finally, we included 23 records 10,13,20‐41 in the review. A total of 21 studies, 10,13,20–22,24,25,27,29–41 comprising 2,839 participants, were included in NMA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 3,228 were excluded and 190 records passed for full‐text screening, of which 167 lacked the eligibility criteria. Finally, we included 23 records 10,13,20‐41 in the review. A total of 21 studies, 10,13,20–22,24,25,27,29–41 comprising 2,839 participants, were included in NMA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to the previous studies [ 34 ], the difference between the SFGS score before and after treatment in the oral administration of prednisolone tablets group was 32.3, with a standard deviation of 8.1. The SFGS score before and after treatment for oral administration of prednisolone tablets combined with electroacupuncture intervention group reached up to 38.3, and the standard deviation was recorded 1.…”
Section: Method/designmentioning
confidence: 93%
“…The analysis (eight trials, 1,365 participants) suggests that antivirals plus corticosteroids reduces the incidence of incomplete recovery when compared either to corticosteroids alone (RR = 0.61, 95% confidence interval [CI] = 0.39 to 0.97, absolute risk difference [ARD] = 6.5%, number needed to treat [NNT] = 15; quality of evidence = low) or to placebo or no treatment (RR = 0.56, 95% CI = 0.41 to 0.76, ARD = 12%, NNT = 8, quality of evidence = low) . Antivirals alone did not improve the risk of incomplete recovery rates when compared to placebo/no treatment (RR = 1.10, 95% CI = 0.87 to 1.40; quality of evidence = low) and increased rates of incomplete recovery when compared to corticosteroids alone (RR = 1.52, 95% CI = 1.08 to 2.12, quality of evidence = low) …”
Section: Narrativementioning
confidence: 99%
“…Unfortunately, the analysis does not control for antiviral type or administration route. Our search identified two clinical trials not reported in the Cochrane analysis that compared either antivirals alone or with corticosteroids to corticosteroids alone. The study by Khedr et al .…”
Section: Caveatsmentioning
confidence: 99%
See 1 more Smart Citation